Low dielectric constant metal-clad laminate and circuit board with curved surface structure
Patent Information
- Application Number
- CN202521770721.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Priority Date
- 2025-06-20
- Filing Date
- 2025-08-19
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2035-08-19
AI Technical Summary
[0003]然而,现有技术中,普通基板一般包括以环氧树脂、聚苯醚树脂、碳氢树脂、BT树脂、聚四氟乙烯中的一种或几种为主体树脂的基底、用于粘接基底的以环氧树脂为主体的FR4粘结剂/片,其中基底的介电常数一般大于2.10,FR4粘结剂/片的介电常数一般大于3.5,导致普通基板的介电常数与介电损耗普遍较高,即使是经过改性的低损耗FR4基板,普遍地其介电常数仍大于3.8,介电损耗仍大于0.007,完全达不到低介电常数(DK<2.0)、低介电损耗(Df<0.005)的性能要求
本公开具备曲面结构的低介电常数覆金属箔层压板和由具备曲面结构的低介电常数覆金属箔层压板加工而成的具备曲面结构的电路板,可满足低介电常数(DK<2)、低损耗(Df<0.005)、金属箔剥离强度>3 lbs/inch的性能要求,能降低高频信号在通过低介电低损耗粘结层与发泡塑料层界面产生的折射与反射损失,能满足金属箔与基底的牢固粘接(>3 lbs/inch),以及粘接的长期可靠性—即不出现因为长期使用或使用环境影响下出现金属箔与基材分层或金属箔鼓泡的情况,且适配制作具备曲面结构的天线。
Smart Images

Figure CN224909735U_ABST
Abstract
Description
Technical Field
[0001] This utility model relates to the application of communication and antennas in the aerospace field, and in particular to a low dielectric constant metal foil laminate and circuit board with a curved structure. Background Technology
[0002] Antennas are key components of communication and radar systems, and antenna arrays fabricated using printed circuit boards (PCBs) are widely used due to their low cost, ease of fabrication, and high precision. However, the design, structure, size, and performance of an antenna are closely related to the dielectric properties of the PCB substrate material. For example, a low dielectric constant (DK<2) can effectively increase antenna bandwidth and reduce signal delay, while low dielectric loss (Df<0.005) can improve antenna gain and energy efficiency. Therefore, reducing the dielectric constant and dielectric loss of the substrate is an important research topic in this field.
[0003] However, in the prior art, ordinary substrates generally include a base made of one or more of the following resins as the main components: epoxy resin, polyphenylene ether resin, hydrocarbon resin, BT resin, and polytetrafluoroethylene, and an epoxy resin-based FR4 adhesive / sheet used to bond the base. The dielectric constant of the base is generally greater than 2.10, and the dielectric constant of the FR4 adhesive / sheet is generally greater than 3.5. This results in generally high dielectric constant and dielectric loss of ordinary substrates. Even modified low-loss FR4 substrates generally still have a dielectric constant greater than 3.8 and a dielectric loss greater than 0.007, which completely fails to meet the performance requirements of low dielectric constant (DK<2.0) and low dielectric loss (Df<0.005).
[0004] In addition, most existing ordinary substrates are planar, which is not suitable for non-planar types, such as antennas with curved structures. Utility Model Content
[0005] The main objective of this invention is to provide, on the one hand, a low dielectric constant metal foil laminate with a curved structure to at least partially solve the above-mentioned problems; on the other hand, to provide a circuit board made from the aforementioned low dielectric constant metal foil laminate with a curved structure, wherein the antenna made from the circuit board can effectively increase the antenna bandwidth and reduce the signal delay, while also improving the antenna gain and energy efficiency.
[0006] As the first aspect of the present utility model, to achieve the above objectives, the present utility model provides a low dielectric constant metal-clad laminate with a curved surface structure, comprising: at least one layer of metal foil, at least one low-dielectric low-loss adhesive layer, and at least one foamed plastic layer; at least one low-dielectric low-loss adhesive layer is disposed between the metal foil and the foamed plastic layer; the metal foil, the low-dielectric low-loss adhesive layer and the foamed plastic layer are stacked to form a layered structure with a curved surface.
[0007] Preferably, the metal foil comprises one or more of copper foil, aluminum foil, stainless steel, and embedded resistor copper foil.
[0008] Preferably, the thickness of the metal foil is between 8 micrometers and 200 micrometers.
[0009] Preferably, one of the characteristics of the foamed plastic layer is that its dielectric constant is less than 2.00.
[0010] Preferably, the layered structure has a dielectric constant DK<2.0, a dielectric loss Df<0.005, and a metal foil peel strength >3lbs / inch.
[0011] Preferably, the first feature of the low-dielectric low-loss adhesive layer is that the dielectric constant of the low-dielectric low-loss adhesive layer is 2.0<DK<3.1, and the dielectric loss of the low-dielectric low-loss adhesive layer is less than 0.004.
[0012] In the prior art, the dielectric constant of the adhesive layer is often relatively high (for example, the dielectric constant of ordinary epoxy resin is 3.7-4.0, the dielectric constant of thermosetting PI is 4.0, and the dielectric constant of modified polyphenylene ether and TAIC system is 3.2-3.5), while the dielectric constant of the foamed material is often less than 2.0. Therefore, when the adhesive layer with high dielectric constant in the prior art is used, the actual test results of the actually prepared microwave devices often differ greatly from the simulation results. For example, when foamed plastic is used to make a Luneburg lens, epoxy resin adhesion will lead to the above problems, which is mainly caused by microwave refraction and reflection losses resulting from the large difference in dielectric constant between the adhesive layer resin in the prior art and the foamed plastic layer in the present application. (YAN Xiulin, SHI Yunqi, ZHU Lina. Design of Luneburg Lens Antenna Based on Novel Foam Materials[J]. Journal of Electronics & Information Technology, 2022, 44(12): 4111-4115. doi: 10.11999 / JEIT220569).
[0013] Therefore, this disclosure reduces refraction and reflection losses when microwaves pass through the adhesive layer by controlling the dielectric constant and loss of the adhesive layer to be as close as possible to the dielectric constant of the foamed plastic. In particular, for the foamed materials of this disclosure with a dielectric constant of less than 2.0, the difference in dielectric constant between the low-dielectric-loss adhesive layer and the substrate cannot be ignored in the high-frequency and even millimeter-wave bands.
[0014] Preferably, the low-dielectric-low-loss adhesive layer is further characterized in that its glass transition temperature is greater than 240°C.
[0015] In existing technologies, rubber or hydrocarbon rubber is used as the adhesive layer. However, common rubber adhesives, such as butyl rubber and polyisobutyl rubber adhesives, have poor temperature and weather resistance. They are prone to blistering and delamination under long-term high temperature and high humidity conditions, especially in extreme environments. The low-dielectric-loss low-loss adhesive layer described in this disclosure has a glass transition temperature greater than 240 degrees Celsius, which is higher than the glass transition temperature of general cross-linked rubbers and resins. Therefore, the low-dielectric-loss low-loss adhesive layer in this disclosure has better thermal stability.
[0016] Preferably, the low dielectric and low loss adhesive layer is characterized in that the water absorption rate of the low dielectric and low loss adhesive layer is less than 0.3% (tested by immersion in water at 50 degrees Celsius for 48 hours).
[0017] The low-dielectric, low-loss adhesive layer has a water absorption rate of less than 0.3%, which can effectively isolate the influence of environmental humidity changes on the metal foil adhesion and ensure adhesion stability. Existing technologies, such as epoxy resin, cyanate ester resin, and bismaleimide resin, have water absorption rates higher than the above requirements. For example, cyanate ester resin systems are widely used in radar radome materials, such as BASF's 5575-2, Fiberite's X54-2, Hexcel's HX 1584-3, and Dow Chemical's XU-71787. The 701 cyanate ester resin system developed by the Aerospace Materials and Processes Research Institute has the following process requirements: ε=2.8, tanδ=0.009, Tg=205℃. Its water absorption rate after immersion in water at 22℃ for 40 days is 0.73%, significantly higher than the water absorption rate of the low-dielectric, low-loss adhesive layer described in this disclosure.
[0018] The low-dielectric-low-loss adhesive layer disclosed herein may be configured as follows. The main component of the low-dielectric-low-loss adhesive layer is one or a mixture of low-loss crosslinked hydrocarbon polymers or low-loss crosslinked polyphenylene ether polymers. The low-loss crosslinked hydrocarbon polymer includes one or more of the following: butadiene polymers, isoprene polymers, butadiene-styrene rubber, butadiene-styrene block polymers, styrene-isoprene block polymers, styrene-isoprene-styrene block polymers, styrene-polybutadiene-styrene block polymers, divinylbenzene polymers, styrene-divinylbenzene polymers, styrene-butadiene-divinylbenzene polymers, ethylene propylene diene monomer (EPDM) rubber, butyl rubber, and cyclic olefin polymers (e.g., acenaphthene), crosslinked via free radical initiation. The low-loss crosslinked polyphenylene ether polymer comprises a polyphenylene ether polymer with vinyl or allyl active groups modified at the polymer's end groups or side groups, crosslinked via free radical initiation.
[0019] Preferably, the low-dielectric-low-loss adhesive layer has a thickness of 20 micrometers to 200 micrometers.
[0020] Preferably, the foamed plastic layer, as a second feature, comprises one or more of polymethacrylamide foam material, porous / foamed polyimide material, and foamed polyester material.
[0021] Preferably, the low-dielectric-low-loss adhesive layer may contain fillers. The fillers may include one or a mixture of silica particles, hollow silica, porous silica, hollow glass microspheres, zeolite, molecular sieves, diatomaceous earth, boron nitride, and silicon nitride.
[0022] Preferably, the layered structure includes a curved metal foil, a curved foamed plastic layer, and a curved low-dielectric-low-loss adhesive layer located between the curved metal foil and the foamed plastic layer, wherein the curved metal foil, the curved foamed plastic layer, and the curved low-dielectric-low-loss adhesive layer are configured into a semi-annular structure.
[0023] Preferably, the curved metal foil can be selectively configured on the concave or convex surface of the semi-annular structure.
[0024] Preferably, the layered structure includes an outermost curved metal foil, an innermost semi-cylindrical foamed plastic layer, and a first curved foamed plastic layer, a second curved foamed plastic layer, and a third curved foamed plastic layer arranged sequentially from the inside out between the curved metal foil and the semi-cylindrical foamed plastic layer. The layered structure also includes a curved low-dielectric-low-loss adhesive layer for bonding the curved metal foil to the third curved foamed plastic layer, the third curved foamed plastic layer to the second curved foamed plastic layer, the second curved foamed plastic layer to the first curved foamed plastic layer, and the first curved foamed plastic layer to the semi-cylindrical foamed plastic layer. The curved metal foil, the third curved foamed plastic layer, the second curved foamed plastic layer, the first curved foamed plastic layer, and the semi-cylindrical foamed plastic layer together form a semi-cylindrical structure.
[0025] Preferably, the third curved foam plastic layer, the second curved foam plastic layer, the first curved foam plastic layer, and the semi-cylindrical foam plastic layer have different densities and dielectric constants.
[0026] Preferably, the curved metal foil is copper foil, each curved foamed plastic layer is foamed PMI, and the curved low dielectric low loss adhesive layer is a semi-cured adhesive sheet made of low loss cross-linked hydrocarbon polymer as the main resin.
[0027] As another aspect of this disclosure, this disclosure also provides an electrical and electronic component made from the aforementioned low dielectric constant metal foil laminate with a curved structure, preferably a circuit board with a curved structure.
[0028] The advantages of this utility model are: This disclosure discloses a low-dielectric-constant metal foil laminate with a curved structure and a circuit board with a curved structure processed from the low-dielectric-constant metal foil laminate with a curved structure. It can meet the performance requirements of low dielectric constant (DK<2), low loss (Df<0.005), and metal foil peel strength >3 lbs / inch. It can reduce the refraction and reflection loss of high-frequency signals at the interface between the low-dielectric-constant low-loss adhesive layer and the foamed plastic layer. It can meet the requirements of strong adhesion between the metal foil and the substrate (>3 lbs / inch) and long-term reliability of the adhesion—that is, no delamination or blistering of the metal foil between the metal foil and the substrate due to long-term use or the influence of the use environment. It is also suitable for manufacturing antennas with curved structures.
[0029] Meanwhile, the antenna fabricated using the aforementioned circuit board can effectively increase antenna bandwidth and reduce signal delay, while also improving antenna gain and energy efficiency. Attached Figure Description
[0030] Figure 1 This is an enlarged schematic diagram of the layered structure involved in Example 1.
[0031] Figure 2 This is an enlarged schematic diagram of the layered structure involved in Example 2. Detailed Implementation
[0032] The technical solutions of the present utility model will be clearly and completely described below with reference to the accompanying drawings of the embodiments. Obviously, the described embodiments are only some embodiments of the present utility model, and not all embodiments. Based on the embodiments of the present utility model, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the protection scope of the present utility model.
[0033] This utility model discloses a low dielectric constant metal foil laminate with a curved structure. The design concept is that the laminate includes: at least one metal foil, at least one low dielectric low loss adhesive layer, and at least one foamed plastic layer. Among them, at least one low dielectric low loss adhesive layer is provided between the metal foil and the foamed plastic layer. The metal foil, the low dielectric low loss adhesive layer, and the foamed plastic layer are stacked to form a layered structure with a curved surface.
[0034] Specifically, for the selection of materials for the low-dielectric-low-loss adhesive layer, the main component is limited to one or a mixture of low-loss crosslinked hydrocarbon polymers or low-loss crosslinked polyphenylene ether polymers. Specifically: the low-loss crosslinked hydrocarbon polymer may include one or more of the following: butadiene polymer, isoprene polymer, butadiene-styrene rubber, butadiene-styrene block polymer, styrene-isoprene block polymer, styrene-isoprene-styrene block polymer, styrene-polybutadiene-styrene block polymer, divinylbenzene polymer, styrene-divinylbenzene polymer, styrene-butadiene-divinylbenzene polymer, ethylene propylene diene monomer (EPDM) rubber, butyl rubber, and cyclic olefin polymers, crosslinked by free radical initiation; the low-loss crosslinked polyphenylene ether polymer may be a polyphenylene ether polymer in which the end groups or side groups of the polymer are modified with vinyl or allyl active groups, crosslinked by free radical initiation. After the aforementioned material selection, the dielectric constant of the low-dielectric-low-loss adhesive layer can be reduced to 3.0.
[0035] Regarding the selection of materials for the foamed plastic layer, the foamed plastic layer can be one or more of polymethacrylamide foam material, porous / foamed polyimide material, and foamed polyester material. After the aforementioned material selection, the dielectric constant of the foamed plastic layer can be less than 2.00.
[0036] In existing conventional substrates, the dielectric constant of the common adhesive layer is often relatively high (e.g., the dielectric constant of common epoxy resin is 3.7-4.0, the dielectric constant of thermosetting PI is 4.0, and the dielectric constant of modified polyphenylene ether and TAIC system is 3.2-3.5). The common base layer is based on one or more of epoxy resin, polyphenylene ether resin, hydrocarbon resin, BT resin, and polytetrafluoroethylene, and its dielectric constant is generally greater than 2.10. Therefore, the dielectric constant and dielectric loss of conventional substrates are generally high. In this application, the dielectric constant of the foamed material is less than 2.0, and the dielectric constant of the low dielectric and low loss adhesive layer can be reduced to 3.0, close to the dielectric constant of the foamed material. Thus, the low dielectric constant metal-clad laminate can meet the performance requirements of low dielectric constant (DK<2.0) and low loss (Df<0.005).
[0037] However, when using high dielectric constant bonding layers in existing technologies, the actual test results of the fabricated microwave devices often differ significantly from the simulation results. For example, when using foamed plastic to fabricate Luneburg lenses, the epoxy resin bonding leads to the above-mentioned problems. The main reason is that the large difference in dielectric constant between the bonding layer resin and the foam layer results in microwave refraction and reflection losses. (YAN Xiulin, SHI Yunqi, ZHU Lina. Design of Luneburg Lens Antenna Based on Novel Foam Materials[J]. Journal of Electronics&Information Technology, 2022,44(12): 4111-4115. doi: 10.11999 / JEIT220569).
[0038] In this application, the metal foil can be selected from one or more of copper foil, aluminum foil, stainless steel, and embedded copper foil, and the thickness is limited so that the thickness of the metal foil is 8 micrometers to 200 micrometers.
[0039] Regarding the low-dielectric-low-loss adhesive layer, the thickness is limited to 20 micrometers to 200 micrometers.
[0040] In this application, the structure and materials of the low dielectric and low loss adhesive layer are further optimized. The low dielectric and low loss adhesive layer includes a filler, which includes one or a mixture of silica particles, hollow silica, porous silica, hollow glass microspheres, zeolite, molecular sieve, diatomaceous earth, boron nitride, and silicon nitride.
[0041] In this application, the dielectric loss tangent of the low dielectric low loss adhesive layer at a frequency of 10 GHz can reach less than 0.0040°, the glass transition temperature of the low dielectric low loss adhesive layer is greater than 240°C, and the water absorption rate of the low dielectric low loss adhesive layer is less than 0.3% (tested by immersion in 50°C water for 48 hours).
[0042] It should be noted that in the prior art, rubber or hydrocarbon rubber is used as the adhesive layer. However, ordinary rubber adhesives, such as butyl rubber and polyisobutyl rubber adhesives, have poor temperature resistance and weather resistance. They are prone to blistering and delamination under long-term high temperature and high humidity, especially in extreme environments. In contrast, the glass transition temperature of the low dielectric and low loss adhesive layer described in this invention is greater than 240 degrees Celsius, which is higher than the glass transition temperature of general cross-linked rubbers and resins. Therefore, the low dielectric and low loss adhesive layer in this disclosure has better thermal stability.
[0043] In this disclosure, the water absorption rate of the low-dielectric, low-loss adhesive layer is less than 0.3%, which can effectively isolate the influence of environmental humidity changes on the metal foil adhesion and ensure adhesion stability. In contrast, the water absorption rates of existing technologies, such as epoxy resin, cyanate ester resin, and bismaleimide resin, are all higher than the above requirements. For example, cyanate ester resin systems are widely used in the wave-transparent materials of radomes, such as BASF's 5575-2, Fiberite's X54-2, Hexcel's HX 1584-3, and Dow Chemical's XU-71787. The 701 cyanate ester resin system developed by the Aerospace Materials and Processes Research Institute has the following process requirements: ε=2.8, tanδ=0.009, Tg=205℃, and a water absorption rate of 0.73% after immersion in water at 22℃ for 40 days, which is significantly higher than the water absorption rate of the low-dielectric, low-loss adhesive layer described in this invention.
[0044] The following specific embodiments illustrate the detailed preparation method of the aforementioned low dielectric constant metal foil laminate with curved surface structure. This preparation method includes the following steps: S1. Prepare a low-dielectric-low-loss adhesive layer; S2. Place the low dielectric and low loss adhesive layer between the metal foil and the foamed plastic layer to form a multilayer structure; S3. Place the above multi-layer structure in a molding machine. Under certain temperature and pressure, the adhesive layer cross-links, and at the same time, the metal foil and the foamed plastic layer are bonded together.
[0045] In this embodiment, the method for preparing the low-dielectric-low-loss adhesive layer described in S1 can be exemplified as follows: For example, a horizontal coating method can be used, in which a composition of resin, initiator, filler, etc., is formulated into a slurry, which is then coated onto a base film. After removing the solvent, partial curing occurs to form a semi-cured adhesive sheet, which serves as a low-dielectric-low-loss adhesive layer in the laminate. Alternatively, an dip-coating method can be used, in which the aforementioned slurry is coated onto both sides of the fiberglass cloth, after removing the solvent, partial curing occurs to form a semi-cured adhesive sheet.
[0046] It should be noted that in this embodiment: a low-loss cross-linked hydrocarbon polymer can be selected as the main resin to make the semi-cured adhesive sheet, which includes fillers; the metal foil is TWL-HP 1 oz copper foil from Luxembourg Circuit Copper Foil Factory; and the material of the foamed plastic layer is foamed PMI.
[0047] The temperature in S3 must meet the following two conditions: (A) it can initiate the cross-linking reaction of the low dielectric and low loss adhesive layer; (B) it will not cause irreversible deformation of the foamed plastic layer.
[0048] The pressure described in S3 is not limited in this invention, provided that it can effectively bond the material without causing irreversible deformation of the foamed plastic layer.
[0049] It should be noted that cross-linking and bonding can be carried out within the range of temperature: 80℃~300℃, pressure: 0.1kg / cm²~200kg / cm², and time: 1 minute~10 hours. More preferably, it can be carried out within the range of temperature: 150℃~250℃, pressure: 1kg / cm²~30kg / cm², and time: 1 minute~2 hours.
[0050] The low dielectric constant metal foil laminate with curved surface structure prepared by the above method can also be used to manufacture electrical and electronic components. Specifically, circuit boards can also be made using the low dielectric constant metal foil laminate with curved surface structure as raw material.
[0051] The following describes the low dielectric constant metal foil laminate with curved structure using a specific layered structure. It comprises a metal foil, a low dielectric low loss adhesive layer, and a foamed plastic layer. The metal foil, the low dielectric low loss adhesive layer, and the foamed plastic layer are stacked to form a layered structure with curved surface. Example
[0052] Specifically, refer to Figure 1 In this embodiment, the layered structure with curved surface includes a curved metal foil 11, a curved foamed plastic layer 12, and a curved low-dielectric-low-loss adhesive layer 13 located between the curved metal foil 11 and the foamed plastic layer 12. The curved metal foil 11, the curved foamed plastic layer 12, and the curved low-dielectric-low-loss adhesive layer 13 are configured into a semi-annular structure.
[0053] Specifically, in this embodiment, the curved metal foil 11 is disposed on the outer convex surface of the semi-annular structure; in other embodiments, it is also permissible to dispose of it on the inner concave surface.
[0054] Regarding the selection of materials for the curved metal foil 11, the curved foamed plastic layer 12, and the curved low-dielectric-low-loss adhesive layer 13, in this embodiment, the specific details are as follows: the curved metal foil 11 uses TWL-HP Hoz copper foil from Luxembourg Circuit Copper Foil Factory; the curved foamed plastic layer 12 is processed from Cascell 75HF by Zhejiang Zhongke Hengtai New Material Technology Co., Ltd. Figure 1 The curved foamed PMI material shown has a thickness of 6.0 mm; the curved low-dielectric-low-loss adhesive layer 13 is a semi-cured adhesive sheet made of low-loss cross-linked hydrocarbon polymer as the main resin, developed by the applicant (Ningbo Turbulent Electronic Materials Co., Ltd.), model HM30S, with a thickness of 50 micrometers, containing fillers, and has a dielectric constant of 3.00 at 10 GHz, a dielectric loss of 0.0026 at 10 GHz, a glass transition temperature greater than 280 degrees Celsius, and a water absorption rate of 0.01% (50 degrees Celsius, 48h).
[0055] During hot pressing, the aforementioned layered structure is placed in a mold with a custom curved surface. The mold is placed in a molding press with a pressure of 2.0 MPa, a temperature of 190°C, and a lamination time of 2 hours to obtain a low-dielectric-constant metal-coated foil laminate with a curved surface structure. Using the GB / T 4722 7.2 method, the copper foil peel strength in the receiving state is tested to be: P / S = 4.7 lbs / inch. After the low-dielectric-constant metal-coated foil laminate with the curved surface structure is subjected to a 96-hour high and low temperature cycling test (-40°C to 80°C), the copper foil does not delaminate or blister, and the peel strength is tested to be: P / S = 4.5 lbs / inch, with almost no loss in peel strength.
[0056] The surface in this embodiment is only an example and is not limited to the curvature, radius, etc. of the surface.
[0057] This embodiment can fabricate a curved low-dielectric substrate to meet the requirements of conformal array antennas, that is, to conform the antenna array surface to the surface of the carrier (aircraft, missile, satellite, etc.) without compromising the carrier's shape, structure, and aerodynamic characteristics. The conductor surface formed by the copper foil can be processed on any side, which can be a concave surface, a convex surface, or both.
[0058] It should be noted that in other embodiments, the low-dielectric-low-loss adhesive layer may also contain reinforcing materials, such as glass fiber reinforcing materials. Example
[0059] Specifically, refer to Figure 2In this embodiment, the layered structure includes an outermost curved metal foil 21, an innermost semi-cylindrical foamed plastic layer 22, and a first curved foamed plastic layer 23, a second curved foamed plastic layer 24, and a third curved foamed plastic layer 25 arranged sequentially from the inside out between the curved metal foil 21 and the semi-cylindrical foamed plastic layer 22. The layered structure also includes a curved low-dielectric low-loss adhesive layer 26 for bonding the curved metal foil 21 to the third curved foamed plastic layer 25, the third curved foamed plastic layer 25 to the second curved foamed plastic layer 24, the second curved foamed plastic layer 24 to the first curved foamed plastic layer 23, and the first curved foamed plastic layer 23 to the semi-cylindrical foamed plastic layer 22. The curved metal foil 21, the third curved foamed plastic layer 25, the second curved foamed plastic layer 24, the first curved foamed plastic layer 23, and the semi-cylindrical foamed plastic layer 22 together form a semi-cylindrical structure.
[0060] Furthermore, the density and dielectric constant of the third curved foam plastic layer 25, the second curved foam plastic layer 24, the first curved foam plastic layer 23, and the semi-cylindrical foam plastic layer 22 are all different.
[0061] In this embodiment, the selection of materials for the curved metal foil 21, each curved foamed plastic layer, and the curved low-dielectric-low-loss adhesive layer 26 is as follows: the curved metal foil 21 is TWL-HP Hoz copper foil from Luxembourg Circuit Copper Foil Factory; each curved foamed plastic layer uses PMI foam with different densities and dielectric constants; wherein, the density of the third curved foamed plastic layer 25 is 76 kg / m³, DK = 1.10; the density of the second curved foamed plastic layer 24 is 257 kg / m³, DK = 1.34; the density of the first curved foamed plastic layer 23 is 468 kg / m³, DK = 1.64; and the density of the semi-cylindrical foamed plastic layer 22 is 634 kg / m³. m³, DK=1.88; the curved low dielectric and low loss adhesive layer 26 is a semi-cured adhesive sheet of model HM30S, which is made of low-loss cross-linked hydrocarbon polymer as the main resin and is independently developed by the applicant (Ningbo Turbulent Electronic Materials Co., Ltd.). It contains silica filler, has a thickness of 50 micrometers, a dielectric constant of 3.00 at 10 GHz, a dielectric loss of 0.0026 at 10 GHz, a glass transition temperature greater than 280 degrees Celsius, and a water absorption rate of 0.01% (50 degrees Celsius, 48h).
[0062] The layered semi-cylindrical structure described above was placed in a molding machine at a pressure of 0.4 MPa, a temperature of 190℃, and a lamination time of 90 min to obtain a multilayer semi-cylindrical material with a gradient change in dielectric constant from the outermost to the innermost layer. Using the GB / T 4722 7.2 method, the peel strength of the copper foil in the receiving state was tested to be: P / S = 4.7 lbs / inch. After subjecting the low-dielectric material substrate to a 96-hour high-low temperature cycling test (-40℃—80℃), the copper foil did not delaminate or blister, and the peel strength was tested to be: P / S = 4.3 lbs / inch, showing no loss in peel strength.
[0063] This structure can be used to fabricate cylindrical lens antennas. For example, two semi-cylinders can be bonded together to form a single cylindrical structure, and the antenna array can be directly developed and etched on the outer copper surface.
[0064] By bonding a curved low-dielectric-loss low-loss adhesive layer (DK = 2.00–3.10), the structure and fabrication method provided in this application have a dielectric constant close to that of the PMI foam material (DK = 1.10–1.88), resulting in a low refractive index for microwaves. Using the structural materials of this application to fabricate microwave lenses or lens antennas, the gain test and simulation results show a smaller difference compared to existing technologies. In contrast, existing technologies primarily use epoxy resin adhesives. There are many types and formulations of epoxy resin adhesives, generally consisting of various epoxy resins followed by epoxy resin curing agents. While the electrical properties of different epoxy resin adhesive formulations vary, they all possess a relatively high dielectric constant. In microwave lenses, this high-dielectric-constant layer has a higher refractive index, refracting some of the energy that should be concentrated on the main lobe to the side lobes, leading to discrepancies with simulation results and an overestimation of the side lobe gain. (YAN Xiulin, SHI Yunqi, ZHU Lina. Design of Luneburg Lens Antenna Based on Novel Foam Materials[J]. Journal of Electronics&Information Technology, 2022, 44(12): 4111-4115. doi: 10.11999 / JEIT220569).
[0065] It should be noted that in the above figures, the same component name is labeled with different numbers. The main reason is to clearly express the component name specifically referred to in each embodiment. This does not affect the scope of protection of the claims of this application.
[0066] The above description is only a preferred embodiment of the present utility model and does not limit the patent scope of the present utility model. All equivalent structural transformations made under the inventive concept of the present utility model using the contents of the present utility model specification and drawings, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present utility model.
Claims
1. A low dielectric constant metal foil laminate with a curved surface structure, characterized in that, comprising: at least one metal foil layer, at least one low-dielectric low-loss adhesive layer, and at least one foamed plastic layer, wherein at least one low-dielectric low-loss adhesive layer is disposed between the metal foil and the foamed plastic layer; the metal foil, the low-dielectric low-loss adhesive layer and the foamed plastic layer are stacked to form a layered structure with a curved surface.
2. The low dielectric constant metal foil laminate with a curved structure as described in claim 1, characterized in that: The metal foil comprises one of copper foil, aluminum foil, stainless steel, and embedded resistor copper foil; the thickness of the metal foil ranges from 8 micrometers to 200 micrometers.
3. The low dielectric constant metal foil laminate with a curved structure as described in claim 1, characterized in that: The layered structure has a dielectric constant DK < 2.0, a dielectric loss Df < 0.005, and a metal foil peel strength > 3 lbs / inch; the dielectric constant of the low-dielectric low-loss adhesive layer is 2.0 < DK < 3.1, and the dielectric loss of the low-dielectric low-loss adhesive layer is less than 0.004; the glass transition temperature of the low-dielectric low-loss adhesive layer is higher than 240°C; the water absorption of the low-dielectric low-loss adhesive layer is less than 0.3%; the thickness of the low-dielectric low-loss adhesive layer ranges from 20 micrometers to 200 micrometers.
4. The low dielectric constant metal foil laminate with a curved structure as described in claim 1, characterized in that: The main component of the low-dielectric low-loss adhesive layer is one of a low-loss crosslinked hydrocarbon polymer or a low-loss crosslinked polyphenylene ether polymer; The low-loss crosslinked hydrocarbon polymer is one selected from the group consisting of butadiene polymer, isoprene polymer, butadiene-styrene rubber, butadiene-styrene block polymer, styrene-isoprene block polymer, styrene-isoprene-styrene block polymer, styrene-polybutadiene-styrene block polymer, divinylbenzene polymer, styrene-divinylbenzene polymer, styrene-butadiene-divinylbenzene polymer, ethylene propylene diene monomer rubber, butyl rubber, and cycloolefin polymer, which is crosslinked via free radical initiation; The low-loss crosslinked polyphenylene ether polymer is formed by subjecting a polyphenylene ether polymer modified with vinyl or allyl reactive groups at the terminal groups or side groups of the polymer to crosslinking via free radical initiation.
5. The low dielectric constant metal foil laminate with a curved surface structure as described in claim 1, characterized in that: The low-dielectric low-loss adhesive layer comprises a filler, and the filler is one selected from the group consisting of silica particles, hollow silica, porous silica, hollow glass microspheres, zeolite, molecular sieve, diatomaceous earth, boron nitride, and silicon nitride.
6. The low dielectric constant metal foil laminate with a curved surface structure as described in claim 1, characterized in that: The foamed plastic layer has a dielectric constant of less than 2.00; The foamed plastic layer is one selected from the group consisting of polymethacrylimide foam material, porous / foamed polyimide material, and foamed polyester material.
7. The low dielectric constant metal foil laminate with a curved surface structure as described in claim 1, characterized in that: The layered structure comprises a curved metal foil, a curved foamed plastic layer, and a curved low-dielectric low-loss adhesive layer located between the curved metal foil and the foamed plastic layer, and the curved metal foil, the curved foamed plastic layer, and the curved low-dielectric low-loss adhesive layer are configured into a semi-annular structure.
8. The low dielectric constant metal foil laminate with a curved surface structure as described in claim 7, characterized in that: The curved metal foil can be selectively disposed on either the inner concave surface or the outer convex surface of the semi-annular structure; The curved metal foil is a copper foil, each curved foamed plastic layer is foamed PMI, and the curved low-dielectric low-loss adhesive layer is constructed from a semi-cured adhesive sheet made of a low-loss crosslinked hydrocarbon polymer as the main resin.
9. The low dielectric constant metal foil laminate with a curved surface structure as described in claim 1, characterized in that: The layered structure includes an outermost curved metal foil, an innermost semi-cylindrical foamed plastic layer, and a first curved foamed plastic layer, a second curved foamed plastic layer, and a third curved foamed plastic layer arranged sequentially from the inside out between the curved metal foil and the semi-cylindrical foamed plastic layer. The layered structure also includes a curved low-dielectric-low-loss adhesive layer for bonding the curved metal foil to the third curved foamed plastic layer, the third curved foamed plastic layer to the second curved foamed plastic layer, the second curved foamed plastic layer to the first curved foamed plastic layer, and the first curved foamed plastic layer to the semi-cylindrical foamed plastic layer. The curved metal foil, the third curved foamed plastic layer, the second curved foamed plastic layer, the first curved foamed plastic layer, and the semi-cylindrical foamed plastic layer together form a semi-cylindrical structure. The third curved foam plastic layer, the second curved foam plastic layer, the first curved foam plastic layer, and the semi-cylindrical foam plastic layer have different densities and dielectric constants; The curved metal foil is copper foil, each curved foamed plastic layer is foamed PMI, and the curved low dielectric low loss adhesive layer is a semi-cured adhesive sheet made of low loss cross-linked hydrocarbon polymer as the main resin.
10. A circuit board, characterized in that, The curved surface structure according to any one of claims 1-9 It is made from low dielectric constant metal foil laminate.